1996
DOI: 10.3109/00498259609046694
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of diflunisal in liver and kidney microsomes of rat and man

Abstract: 1. The glucuronidation of diflunisal to its phenolic (DPG) and acyl glucuronide (DAG) was measured in vitro using microsomes prepared from rat (n = 4) and human (n = 6) liver and kidney tissue. UGT activities towards bilirubin, 4-nitrophenol and (-)-morphine were also determined. 2. beta-Glucuronidase activity towards phenolphthalein glucuronide was much lower in microsomes prepared from human liver (45.2 +/- 3.1 Fishman Units/mg protein), human kidney (22.0 +/- 3.3 FU/mg), and rat kidney (25.1 +/- 2.5 FU/mg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…In this study, the formation of M3G was determined (Table 1). There was no measurable M3G formation in kidney microsomal incubations, which is consistent with the results reported by Brunelle and Verbeeck (1996). CRI did not affect hepatic glucuronidation of morphine at the 3-position, whereas the formation of M3G was decreased by ϳ24% in the CPF ( p Ï­ 0.06) and the CRI ( p Ï­ 0.07) groups compared with the control group.…”
Section: Yu Et Alsupporting
confidence: 81%
“…In this study, the formation of M3G was determined (Table 1). There was no measurable M3G formation in kidney microsomal incubations, which is consistent with the results reported by Brunelle and Verbeeck (1996). CRI did not affect hepatic glucuronidation of morphine at the 3-position, whereas the formation of M3G was decreased by ϳ24% in the CPF ( p Ï­ 0.06) and the CRI ( p Ï­ 0.07) groups compared with the control group.…”
Section: Yu Et Alsupporting
confidence: 81%
“…Brunelle and Verbeeck (1993) investigated the effect of saccharolactone on the acyl glucuronidation of diflunisal in rat liver microsomes and found that the maximum rate increased 2-fold with the addition of 4 mM saccharolactone. Follow-up experiments showed similar results both in other microsomal systems (human) (Brunelle & Verbeeck 1996), and in-vivo (rat) (Brunelle & Verbeeck 1997). Other investigators have found similar results, supporting the use of saccharolactone in in-vitro glucuronidation experiments (Gigon & Bickel 1979;Haaz et al 1997;Kemper & Nabb 2005).…”
supporting
confidence: 67%
“…Carboxylate NSAIDs are excreted to a variable extent in vivo as glucuronides, either as the conjugate of the parent carboxylic acid or a hydroxylated metabolite, with only a small fraction of the dose eliminated as unchanged drug in urine [1]. NSAID metabolism has also been investigated in vitro , particularly with human liver microsomes (HLM) as the enzyme source [2–4], and the liver is normally considered the major organ responsible for drug metabolic clearance [5]. However, significant glucuronidation activity towards endogenous compounds and xenobiotics has been reported for human kidney tissue.…”
Section: Introductionmentioning
confidence: 99%